Formação continuada de professores e desenvolvimento institucional de escolas públicas: articulações, dificuldades e possibilidades - Gama, Maria Eliza Rosa (2007)
To understand the development and the functioning of the carried out Processes of continued education in Schools of Basic Education (EEB) seems to be undelayable investment of teachers in professional exercise qualification and point out conditions to put changes into effect in their pedagogical practices. Our research, accomplished in the years 2005 and 2006, sought to find answers for the following problem: Which aspects characterize and which ones work as condition to the elaboration and accomplishment process of continued education of teachers in the Schools of Basic Education of Santa Maria and which relations are established between these aspects? It is a qualitative research that involved as research space, 4 schools of Basic Education of the Public Net of the Santa Maria city. We used as sources of information, the formative meeting carried out in these schools, besides the discourse of 50 persons who constructed our real sample of research, they are: four professional responsible for planning and developing the actions of continued education of the 4 investigated EEB; 38 teachers who had participated in the carried out formative meeting in the schools; 8 professionals invited to carry out the formative meetings with the teachers. We used as an instrument, to collect information, participated observations, collective and individuals interviews and scripts. We identified some aspects of the meetings organization and functioning which have limited the education to be a moment of these teachers collective production. We pointed out that continued education has been organized, in general, independent of the teachers and school s needs and difficulties. The teachers have a minimal participation on the decisions concerning the processes offered to them. Normally, the teacher trainers do not have knowledge about school contexts and about the teachers for which they carry out the meeting. The teachers, in turn, believe that the solution for their problems is in knowledge produced outside of the school space, mainly in the academy; therefore, they attribute to the teacher trainers the capacity to solve all the problems and difficulties faced by them. We conclude that, to occur significant changes in these processes, it is necessary to analyze the teacher trainers profile, in the construction of activities that give conditions, in the formative meetings, to teachers construct new knowledge, in the approach of the knowledge dealt with each school and its peculiarities, as well as, in the inclusion of studies on the continued education in order to the teachers adopt more independent and conscientious attitudes concerning their processes of professional development.